2001
DOI: 10.1046/j.1471-4159.2001.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor E2F1 promotes dopamine‐evoked neuronal apoptosis by a mechanism independent of transcriptional activation

Abstract: The E2F1 transcription factor plays an important role in promoting neuronal apoptosis; however, it is not clear how E2F1 does this. Here we show that E2F1 is involved in dopamine (DA)-evoked apoptosis in cerebellar granule neurons (CGNs). E2F1 ±/± CGNs and CGNs expressing an antisense E2F1 cDNA were signi®cantly protected from DA-toxicity relative to controls. The neuronal protection was accompanied by signi®cantly reduced caspase 3 activity. E2F1-mediated neuronal apoptosis did not require activation of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…When tested in several different systems of cultured neurons, the mutant construct promoted death, indicating a derepression mechanism. 94,104 Additional experimental observations further support a mechanism of neuron death driven at least in part by derepression of E2F-regulated genes. A 'decoy' DNA construct consisting of multiple copies of the E2F-binding site also effectively promoted death of neurons.…”
Section: Rb/pocket Proteins and Neuron Deathmentioning
confidence: 76%
See 2 more Smart Citations
“…When tested in several different systems of cultured neurons, the mutant construct promoted death, indicating a derepression mechanism. 94,104 Additional experimental observations further support a mechanism of neuron death driven at least in part by derepression of E2F-regulated genes. A 'decoy' DNA construct consisting of multiple copies of the E2F-binding site also effectively promoted death of neurons.…”
Section: Rb/pocket Proteins and Neuron Deathmentioning
confidence: 76%
“…84,104,[106][107][108][109] Overexpression of E2F1 also accelerated loss of T-antigenexpressing Purkinje cells in transgenic mice. 81 Although such findings can and have been viewed as supporting an E2F-dependent gene activation model of neuron death, there are alternative interpretations.…”
Section: Does E2f-dependent Gene Activation Have a Role In Neuron Death?mentioning
confidence: 95%
See 1 more Smart Citation
“…However, neurons are terminally differentiated and postmitotic, having exited the cell cycle irreversibly. Thus, an increase in the expression of cell cycle proteins may cause unfavorable effects on neurons, specifically inducing the expression of the proapoptotic transcriptional factor E2F-1 (Hou et al, 2001;R.A. Smith et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including our own, have shown that the transcription factor E2F1 plays an important role in modulating ischemiainduced neuronal death (11,19,22,24,44). Adenovirus (Ad)-mediated overexpression of E2F1 in cerebellar granule neurons (CGNs) resulted in neuronal apoptosis (18,20,35), while E2F1-deficient neurons were resistant to death evoked by K ϩ withdrawal (14,44), staurosporine (18), dopamine (19,20), 6-hydroxydopamine (19), and oxygen-glucose deprivation (11). In addition, E2F1 knockout mice were more resistant to ischemia-induced brain damage than their wild-type littermates (32,33).…”
mentioning
confidence: 99%